Structure and Magnetic Properties Zn0.96Cu0.01Ni0.03O Nanoparticles - GÜLER, ADİL (My University, 2019)
Zn0.96Cu0.01Ni0.03O nanoparticles were prepared by sol-gel technique and annealed under wide temperature range (450, 500, 550, 600, 700,800, and 900 0C). To figure out the possible structural phases X-ray diffraction technique (XRD) was used. The lattice parameters were calculatedby Rietveld analysis and correlated by annealing temperatures. For the synthesized nanoparticles, the optimum annealing temperatureswere achieved at 450, 500, and 550 °C and further annealing temperature increment gave rise to secondary NiO peaks. The ScanningElectron Microscope (SEM) images show random ball-shaped particle distribution. Energy dispersive X-ray spectroscopy (EDX) showedonly the peaks belong to the composition. Magnetic measurements were performed using Quantum Design Vibrating Sample Magnetometer(QDVSM) tool for Zn0.96Cu0.01Ni0.03O nanosystems. From the DC magnetic field dependent magnetization curves, clear paramagneticbehavior was revealed for all Cu-Ni co-doped ZnO nanoparticles.

Zn0.96Cu0.01Ni0.03O nanoparçacıkları, sol-gel tekniği ile hazırlanıp geniş sıcaklık aralığında (450, 500, 550, 600, 700, 800, 900 ° C) tavlandı. Olası yapısal fazları belirlemek için X-ışını kırınım tekniği (XRD) kullanılmıştır. Kafes parametreleri Rietveld analizi ile hesaplanmış ve tavlama sıcaklıkları ile ilişkilendirilmiştir. Sentezlenen nanoparçacıklar için, optimum tavlama sıcaklıkları 450, 500 ve 550 ° C’de elde edildi ve ayrıca tavlama sıcaklığı artışı ikincil NiO fazlarına yol açmıştır. Taramalı Elektron Mikroskobu (SEM) görüntüleri rastgele küre şeklindeki parçacık dağılımını göstermektedir. Enerji dağıtıcı X-ışını spektroskopisi (EDX) sadece kompozisyona ait pikleri göstermektedir. Zn0.96Cu0.01Ni0.03O nanoparçacıkları için manyetik ölçümler, Kuantum Dizayn Titreşen Örnek Manyetometresi (QDVSM) kullanılarak yapıldı. DC manyetik alana bağlı mıknatıslanma eğrilerinden, tüm Cu-Ni ortak katkılı ZnO nanoparçacıklarının net paramanyetik davranışı gösterildi.
Zn0.96Cu0.01Ni0.03O Nanoparçacıkların Yapısal ve Manyetik Özellikleri
Keywords: Kimya, Uygulamalı; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler